An unusual presentation of MEN2A. (6th June 2013) - Casey, R; Bell, M; Keane, M; Smyth, A
Abstract : A 35-year-old woman presented with non-specific symptoms of fatigue and weight loss. Radiological investigations diagnosed a metastatic process and large bilateral adrenal masses. Histology from a liver biopsy and skin biopsy confirmed a diagnosis of metastatic medullary thyroid cancer. Further biochemical investigations revealed a positive 24-h urinary metanephrine collection and evidence of primary hyperparathyroidism. Genetic testing confirmed a mutant RET oncogene, confirming our clinical suspicion of multiple endocrine neoplasia type 2 (MEN2A) syndrome. The patient had no family history of endocrine disease and presented with widespread metastatic disease, making this an unusual presentation of MEN2A syndrome. Furthermore cutaneous metastases are rarely encountered in conjunction with metastatic medullary thyroid cancer. This case draws attention to the importance of genetic counselling in first-degree relatives of patients with confirmed MEN2A. This allows for timely diagnosis and reduced morbidity and mortality.